IMPLEMENTASI PROGRAM BANTUAN DANA DAN SEMBAKO BAGI MASYARAKAT TERDAMPAK COVID-19 DI DESA KAASAR KECAMATAN KAUDITAN - PALIT, DEYBI DEBORA; TULUSAN, FEMMY; PALAR, NOVIE (Sam Ratulangi University, 2022)
The social assistance program is one of the components of the social security program which is a form ofrealization of the responsibility of the central government or local government which is very concernedabout the condition of the poor and neglected people. In the current pandemic conditions, people reallyneed attention and assistance from the government to survive. Currently, the government provides socialsecurity to people affected by Covid-19, namely: Direct Cash Assistance-Village Funds, Cash SocialAssistance, Non-Cash Food Assistance, Family Hope Program, Basic Food, and various other assistance.This study discusses the program of financial assistance and basic necessities. The object of research usesthe policy theory of David C. Korten. This study uses a qualitative descriptive research method becausethe descriptive qualitative research method is a research procedure that is focused in depth. Informants inthis study amounted to 13 people consisting of 6 village officials, and 7 people receiving assistance. Datacollection techniques used are observation, interviews, and documentation.The results showed that the implementation of the funding and basic food assistance program in KaasarVillage, Kauditan District based on the policy theory of David C. Korten was not appropriate because thetarget group elements had not been running well. There are still people who do not meet the criteria forgetting assistance, and there are still delays in the distribution of aid, and not all people are unable to getassistance.Keywords: Implementation Program, Fund Assistance and Basic Food